Clinical Cases in Psoriasis - Wu, Jashin J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This title recognises that clinical cases are a key component in modern medical education, assisting the trainee or recertifying clinician to work through unusual cases using best practice techniques. It also acknowledges that psoriasis is an important discipline in this regard since it is a highly visual subject requiring the reader to describe often very subtle differences in the presentation of patients and define accurately the diagnostic and management criteria to base their clinical decision-making on. The objective of this book is to provide readers with an overview of the diagnosis and multidisciplinary management of psoriasis. As part of the Clinical Cases in Dermatology series, the range of titles cover the most common skin problems encountered in clinical practice and many of the rarer diseases that may be encountered by the practicing dermatologist.
12 Year Old with Scaly, Itchy Scalp -- A 54 Year Old with Diffuse Red, Scaly Spots on Entire Body -- Red Rash on Scalp -- 41 Year Old with Nail Deformities -- 69 Year Old with Rash on the Axilla and Groin -- 45 Year Old with Red Rash on Face -- 16 Year Old with Rash on Genitals -- 70 year Old Male with Red Rash on Palms -- Noncompliant 57 Year Old Patient with Psoriasis -- Severely Obese 42 Year Old with Psoriasis -- 62 Year Old Male with Rash Induced by Tumor Necrosis Factor Inhibitor -- 33 Year Old Female with Psoriasis Planning for Pregnancy -- Infected Joint Prosthesis in a 56 Year Old with Psoriasis -- 43 Year Old with Recurrence of Red, Scaly Rash -- Joint Stiffness in a 45 Year Old with Psoriasis -- 69 Year Old with Psoriasis and a History of Skin Cancer -- Herpes Zoster Reactivation in a 40 Year Old With Psoriasis -- Tuberculosis Infection in a 58 Year Old with Psoriasis -- 50 Year Old with Psoriasis and Hepatitis B Virus Infection -- 54 Year Old with Psoriasis and hepatitis C virus infection -- HIV Infection in a 44 Year Old with Psoriasis.
Keywords: Medicine; Dermatology; Medicine & Public Health; Dermatology